Exhaled Nitric Oxide is Decreased by Exposure to the Hyperbaric Oxygen Therapy Environment - Zudin A. Puthucheary; Jia Liu; Michael Bennett; Barbara Trytko; Sharron Chow; Paul S. Thomas (Mediators of Inflammation)
Exhaled nitric oxide (eNO) detects airway inflammation. Hyperbaric oxygen therapy (HBOT) is used for tissue hypoxia, but can cause lung damage. We measured eNO following inhalation of oxygen at different tensions and pressures. Methods. Part 1, eNO was measured before and after HBOT. Part 2, normal subjects breathed 40% oxygen. Results. Baseline eNO levels in patients prior to HBOT exposure were significantly higher than in normal subjects (P < .05). After HBOT, eNO significantly decreased in patients (15.4 ± 2.0 versus 4.4 ± 0.5 ppb, P < .001), but not in normal subjects, after either 100% O2 at increased pressure or 40% oxygen, 1 ATA. In an in vitro study, nitrate/nitrite release decreased after 90 minutes HBOT in airway epithelial (A549) cells. Conclusion. HBO exposure causes a fall in eNO. Inducible nitric oxide synthase (iNOS) may cause elevated eNO in patients secondary to inflammation, and inhibition of iNOS may be the mechanism of the reduction of eNO seen with HBOT.